2018
DOI: 10.1371/journal.pmed.1002645
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing to expand HIV testing among men who have sex with men in China: A closed cohort stepped wedge cluster randomized controlled trial

Abstract: BackgroundHIV testing rates are suboptimal among at-risk men. Crowdsourcing may be a useful tool for designing innovative, community-based HIV testing strategies to increase HIV testing. The purpose of this study was to use a stepped wedge cluster randomized controlled trial (RCT) to evaluate the effect of a crowdsourced HIV intervention on HIV testing uptake among men who have sex with men (MSM) in eight Chinese cities.Methods and findingsAn HIV testing intervention was developed through a national image cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
185
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 132 publications
(196 citation statements)
references
References 40 publications
6
185
0
Order By: Relevance
“…The majority of iTech's studies focus on improving the prevention continuum-including promoting home-based HIV testing as part of the digital intervention [20][21][22]. Within three iTech interventions (MyChoices, LYNX and We Prevent) participants can request home-based HIV/STI test kits via study app.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…The majority of iTech's studies focus on improving the prevention continuum-including promoting home-based HIV testing as part of the digital intervention [20][21][22]. Within three iTech interventions (MyChoices, LYNX and We Prevent) participants can request home-based HIV/STI test kits via study app.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…The lack of an association between participating in online activities and HIV testing may be related to a lack of online intentions being effectively translated into offline behaviors. In addition, subgroups without previous HIV testing may have been particularly likely to test as part of the intervention period [34]. Future studies on social media interventions should provide visual and textual information, engage local communities, and evaluate participant recall.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a secondary analysis of longitudinal data collected as part of a randomized controlled trial that is described in detail elsewhere [34]. The stepped wedge randomized controlled trial collected data from MSM over a 12-month period starting in July 2016 in eight Chinese cities: four cities in Guangdong Province (Guangzhou, Shenzhen, Zhuhai, and Jiangmen) and four cities in Shandong Province (Jinan, Qingdao, Yantai, and Jining).…”
Section: Participant Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Several studies also assessed the efficacy of crowdsourced videos on HIV testing, and largely found that they were non-inferior to regular health marketing campaigns, 17 or only had a positive effect on HIV testing rates through the use of home-based self-testing kits, but not facility-based HIV/STI testing. 22 There are, however, several limitations in the context of reach and feasibility for such interventions. For example, reminder-based and peer education-based interventions require existing health systems that can support such interventions, which may not be feasible in most settings that do not have such services, or where GBQ male-specific clinical services are unavailable due to the criminalisation of sex between men.…”
Section: Open Accessmentioning
confidence: 99%